2022
DOI: 10.1039/d2sc01532c
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule magnets beyond a single lanthanide ion: the art of coupling

Abstract: The promising future of storing and processing quantized information at the molecular level has been attracting the study of Single-Molecule Magnets (SMMs) for almost three decades. Although some recent breakthroughs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 116 publications
1
66
0
Order By: Relevance
“…12,[34][35][36][37][38] For polynuclear SMMs, the intra-molecular magnetic couplings between Ln III ions also need to be addressed since the zerofield quantum tunnelling of magnetisation (QTM) can be effectively suppressed owing to the reduced tunnelling probability for the need to simultaneously flip two magnetic moments. [39][40][41][42][43][44][45][46][47][48][49] Of the major achievements, examples are the record blocking temperature (T B = 80 K) discovery for the mononuclear Dy III metallocene cation, namely, [(Cp iPr5 )Dy (Cp*)] + (Cp iPr5 = penta-iso-propylcyclopentadienyl, Cp* = pentamethylcyclopentadienyl) with a record anisotropy barrier of up to 2217 K, 50 and the enormous coercive magnetic field with a lower bound of 14 T, detected for a mixed-valence di-lanthanide complex [(Cp iPr5 ) 2 Dy 2 I 3 ] at temperatures as high as 60 K. 51 The subcomponent self-assembly approach reveals a more versatile and robust synthetic method compared to the use of pre-synthesis of the ligand to achieve the construction of selfassembled architectures. 52 This method has been widely adopted for the construction of functional polynuclear transition and lanthanide supramolecular architectures, and can yield desired stable aggregates with complex topologies via judicious choice of subcomponent scaffolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[34][35][36][37][38] For polynuclear SMMs, the intra-molecular magnetic couplings between Ln III ions also need to be addressed since the zerofield quantum tunnelling of magnetisation (QTM) can be effectively suppressed owing to the reduced tunnelling probability for the need to simultaneously flip two magnetic moments. [39][40][41][42][43][44][45][46][47][48][49] Of the major achievements, examples are the record blocking temperature (T B = 80 K) discovery for the mononuclear Dy III metallocene cation, namely, [(Cp iPr5 )Dy (Cp*)] + (Cp iPr5 = penta-iso-propylcyclopentadienyl, Cp* = pentamethylcyclopentadienyl) with a record anisotropy barrier of up to 2217 K, 50 and the enormous coercive magnetic field with a lower bound of 14 T, detected for a mixed-valence di-lanthanide complex [(Cp iPr5 ) 2 Dy 2 I 3 ] at temperatures as high as 60 K. 51 The subcomponent self-assembly approach reveals a more versatile and robust synthetic method compared to the use of pre-synthesis of the ligand to achieve the construction of selfassembled architectures. 52 This method has been widely adopted for the construction of functional polynuclear transition and lanthanide supramolecular architectures, and can yield desired stable aggregates with complex topologies via judicious choice of subcomponent scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…12,34–38 For polynuclear SMMs, the intra-molecular magnetic couplings between Ln III ions also need to be addressed since the zero-field quantum tunnelling of magnetisation (QTM) can be effectively suppressed owing to the reduced tunnelling probability for the need to simultaneously flip two magnetic moments. 39–49 Of the major achievements, examples are the record blocking temperature ( T B = 80 K) discovery for the mononuclear Dy III metallocene cation, namely, [(Cp iPr5 )Dy(Cp*)] + (Cp iPr5 = penta-iso-propylcyclopentadienyl, Cp* = pentamethylcyclopentadienyl) with a record anisotropy barrier of up to 2217 K, 50 and the enormous coercive magnetic field with a lower bound of 14 T, detected for a mixed-valence di-lanthanide complex [(Cp iPr5 ) 2 Dy 2 I 3 ] at temperatures as high as 60 K. 51…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of high-performance molecular nanomagnets, lanthanide-based complexes have attracted more attention. , It is because the trivalent lanthanide ions, especially Tb III , Dy III , and Er III ions, possess stronger spin–orbit coupling and a larger spin number, both of which are very important for the occurrence of slow relaxation of magnetization. A recent breakthrough has been made in substituted cyclopentadienyl-ligated dysprosium metallocene, which showed a record energy barrier over 2000 K and a blocking temperature surpassing liquid nitrogen temperature. , The achievements in constructing high-performance mononuclear SMMs recalled the interests in the research of exchange-coupled polynuclear nanomagnets . In fact, integrating lanthanide-based SMMs into coordination polymers provides new opportunities for multifunctional molecular nanomagnets.…”
Section: Introductionmentioning
confidence: 99%
“…Fascinating investigations have focused on single-molecule magnets (SMMs) and single-chain magnets (SCMs), especially the 4f-based family, because strong magnetic anisotropy is available from 4f ions. [1][2][3][4][5][6][7][8][9] In particular, mononuclear lanthanide SMMs, so-called single-ion magnets (SIMs), gained considerable attention since the observation of SIM behaviors in the sandwich Ln(III) mononuclear complexes [Pc 2 Ln] − [N(C 4 -H 9 ) 4 ] + (Ln = Tb, Dy; Pc 2− = dianion of phthalocyanine) in 2003. 10 Layfield et al reported a mononuclear compound [(η 5 -Cp*)Dy(η 5 -Cp iPr5 )][B(C 6 F 5 ) 4 ] ( C p iPr5 : p e n t a -i s opropylcyclopentadienyl; Cp*: pentamethylcyclopentadienyl), 11 in which the blocking temperature (T B ) is above liquid nitrogen temperature in 2018.…”
Section: Introductionmentioning
confidence: 99%